METASOMATIC ZONING: APPEARANCE OF GHOST ZONES IN THE LIMIT OF PURE ADVECTIVE MASS TRANSPORT - Lichtner P.C.; Balashov V.N. (My University, 1993)
The properties of mineral reaction zones which propagate without changing shape are investigated for a hypothetical two-component system involving advective and diffusive transport in a porous medium. Given sufficient time the width of such zones, referred to as ghost zones, is constant and proportional to the characteristic diffusion or dispersion length of the system. The proportionality factor depends only on the equilibrium constants of the reacting minerals and on the composition of the inlet fluid. As the fluid velocity increases the width of the ghost zone decreases in the case of diffusive transport, and remains constant for dispersive transport for a dispersion coefficient proportional to the fluid velocity. This behavior is contrary to that of normal reaction zones which increase in width in proportion to the fluid velocity. For pure advective transport under conditions of local chemical equilibrium, a ghost zone has zero width. Nevertheless, minerals contained in the ghost zone buffer the downstream fluid composition in spite of their material absence, whence the term ghost . By taking into account transport by diffusion or dispersion, the width of a ghost zone has a finite, non-zero value with a well-defined modal composition. In a surface controlled representation of mineral reaction rates for pure advective transport, the width of the ghost zone is finite, but tends towards zero as the kinetic rate constant approaches infinity.